(untitled) (Journal of the College of Basic Education, 2022)
The idea of ​​the current research is crystallized by raising the following questions: How does the symbolic metaphor appear in designing the commercial advertisements? There is a group of methods that make the metaphor part of a visual discourse based on aesthetic expression in design systems in general and in the design of commercial advertisements in particular? To what extent is the symbol an essential element in shaping the visual discourse of commercial advertisements? Thus, the current research aimed to identify the contents of symbolic borrowing and mechanisms of its operation in the design of commercial advertisements. The current research community consists of commercial advertisements implemented by designers for the period 2016-2020. The researcher chose a random sample of (3) samples that were subjected to analysis according to a form that was prepared that included (6) axes, from which (20) paragraphs are related to research topics, the most important Research findings: 1) There are design systems that focused on the principle that the sources of design reality lie in the mind of the designer, so that he can create abstract shapes from them or derive them from reality to show innovative design products. 2) Designers who are distinguished by generating innovative ideas they employ in their designs in general and advertisement in particular, produce specific ideas in their design products that depend on the requirements of the age and its vitality, and that there are multiple activities from which the creator chooses his shapes and this is what we touch in the three samples.